Seasonal change of difference between the ground-based and EP-TOMS satellite ozone measurements - Kulinich, B. V.; Evtushevsky, A. M.; Leonov, N. A.; Milinevsky, G. P. (Ukrainian Antarctic Journal, 2005)
The relative differences between the total ozone data from the Vernadsky Station data and EP-TOMS satellite spectrometer Version 7 values are analyzed. The 2000-2003 period is considered. To estimate the cloudiness influence on data disagreement, comparison was made taking into account the conditions of cloud cover over station. The daily Dobson spectrophotometer measurements were selected to form the data files of “cloudy days” and “cloudless days”. Mean relative differences of -0.6% and 6.9% were obtained for cloudy and clear sky, respectively. Seasonal changes of the data disagreement are different for cloudy and cloudless days. Observations in cloudy conditions show maximum positive difference in summer and negative one in the early spring and later autumn. In cloudless conditions TOMS-Dobson values difference changes with some ascending trend. This analysis confirms the results of previous comparison of the EP-TOMS and Vernadsky ozone data for 1996-2000. The overestimation of the ground-based total ozone by the TOMS values in the clear sky conditions is perhaps caused by an erroneous interpretation of the snow covered surface reflection as the cloudiness one in the TOMS Version 7 ozone retrieval algorithm.